Tempos do cotidiano de uma cooperativa de economia solidária - Arns, Daniela (2017)
Capitalist globalization deepens socioeconomic inequality, unemployment, poverty, the destruction of nature, etc. The Solidarity Economy, on the other hand, appears with a proposal of inclusion of the subjects, bringing in its core associative and cooperative presuppositions, besides valuing the participation, the solidarity and the cooperation. In Rio Grande do Sul, there is an incentive for the development of economic enterprises in solidarity, and where experiences related to cooperativism predominate. In the daily life of each enterprise, time assumes a crucial character. Therefore, this research sought to understand how the different times of daily life are articulated in a cooperative of Solidarity Economy: the satisfaction of the basic necessities, immediate survival; The economic viability of the cooperative; And the incorporation of the principles of the Solidary Economy. Theoretical foundation has passed on the understanding of Time, Agnes Heller's Theory of Daily Life, Work, Cooperativism and Solidary Economy. It was a qualitative research, through a case study, using the critical dialectic method. A cooperative was analyzed with the following criteria: to be functioning for more than five (5) years, in accordance with the principles of Solidarity Economy, of the area of food production, and to be formed by individuals whose main income was from the cooperative. As instruments were used: the semistructured interview and the participant observation. Four (4) members of the cooperative were interviewed with different length of stay. Data recognition was performed through Moraes Content Analysis (1999). This investigation evidenced that the time to satisfy the basic needs of the subject and the time of viability of the cooperative were long. There were different times for incorporation of the principles of solidarity economy, as well as, its exercise is complex and does not necessarily occur in full form. It became evident that the people who make up the cooperative are able to suspend the daily life through creative work, but they do not remain in that sphere all the time.